2021
DOI: 10.20944/preprints202109.0441.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Risk Factors for Cervical Cancer

Abstract: Cervical cancer is the fourth common cancer amongst women worldwide. Environmental factors such as smoking and obesity, and recurrent infection by high-risk human papillomavirus subtypes are known to promote progression towards invasive cervical disease. Infection by high-risk HPV is necessary in most cases but not sufficient to develop invasive cervical cancer. Despite a predicted genetic heritability of between 27-36%, known genetic susceptibility loci that may be tumorigenic or influence host response to in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 157 publications
(191 reference statements)
0
1
0
Order By: Relevance
“…Family studies have demonstrated familial aggregation of cervical cancer consistent with a significant heritable component, with estimates of heritability ranging from 27 to 36% ( 8–11 ). Genome-wide association studies (GWASs) have so far identified consistent genomic regions associated with cervical cancer on chromosomes 6p21.32-33 (the human leukocyte antigen locus), 5p15.3 ( CLPTM1L / TERT ), 17q12 ( GSDMB ) and 2q14 ( PAX8 ) ( 12–16 ) (reviewed in 17 ). These variants, however, may only explain a small proportion of cervical cancer heritability ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Family studies have demonstrated familial aggregation of cervical cancer consistent with a significant heritable component, with estimates of heritability ranging from 27 to 36% ( 8–11 ). Genome-wide association studies (GWASs) have so far identified consistent genomic regions associated with cervical cancer on chromosomes 6p21.32-33 (the human leukocyte antigen locus), 5p15.3 ( CLPTM1L / TERT ), 17q12 ( GSDMB ) and 2q14 ( PAX8 ) ( 12–16 ) (reviewed in 17 ). These variants, however, may only explain a small proportion of cervical cancer heritability ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%